Dynamic population of N2-fixing cyanobacteria in an organic rice field - DIAN HENDRAYANTI; IMAM RUSMANA; DWI ANDREAS SANTOSA; HAMIM (Society for Indonesian Biodiversity, 2019)
Abstract. Hendrayanti D, Rusmana I, Santosa DA, Hamim. 2019. Dynamic population of N2-fixing Cyanobacteria in an organic rice field. Biodiversitas 20: 2883-2890. The existence of free living N2-fixing cyanobacteria in rice fields has been acknowledged as an advantage for rice crops. At present, implementation of organic rice-systems has been increasing as an alternative way for keeping rice fields healthy. Therefore, investigation of N2-fixing cyanobacteria as a part of the soil components is important. Dynamic populations of the filamentous N2-fixing cyanobacteria assemblage in organic rice field at Ciparay, South Bandung, was investigated during the crop’s growth cycle (January-March 2018). Soil samples were collected from four plots of 20 ha rice fields. At each plot, soil from three random stations with three replications was taken using a 3-cm-diameter plastic cylinder. Composite samples from each station were analyzed for colony enumeration (TPC method), relative abundance and frequency, and species identification. The results show that population reached peak on the 80 days after planting (194 x 106 cfu/g soil). Species number decreased following increased density of the rice canopy. Among the 23 morphospecies found along the rice growth, four species were always found during all stages of growth: Halotia wernerae CSO2, Roholtiella mojavensis CSO6, Hapalosiphon welwitschii CSO7, and Desmonostoc danxiaense CSO3. The community of N2-fixing cyanobacteria found in the organic rice field was different to those reported from non-organic rice field.